2010
DOI: 10.1002/pd.2454
|View full text |Cite
|
Sign up to set email alerts
|

Influence of experience, case load, and stage distribution on outcome of endoscopic laser surgery for TTTS—a review

Abstract: A systematic review of endoscopic laser surgery performed in patients with TTTS failed to show a significant impact of high caseloads, disease severity distribution, or improvements in technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 36 publications
(48 reference statements)
0
19
0
Order By: Relevance
“…We and others have restricted surgery to patients with more advanced disease based on the observation that disease progression is not linear and that many lower stage patients spontaneously improve [4]. Several studies and at least one meta-analysis have shown that limiting intervention to stage III and stage IV does not worsen neonatal survival [7,18]. However, this implies that fetuses who undergo surgical intervention later in the disease process are sicker and may not fully recover after the transfusion process has been halted.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We and others have restricted surgery to patients with more advanced disease based on the observation that disease progression is not linear and that many lower stage patients spontaneously improve [4]. Several studies and at least one meta-analysis have shown that limiting intervention to stage III and stage IV does not worsen neonatal survival [7,18]. However, this implies that fetuses who undergo surgical intervention later in the disease process are sicker and may not fully recover after the transfusion process has been halted.…”
Section: Discussionmentioning
confidence: 94%
“…Neonatal survival of at least one twin is 75% to 85%, and overall survival is 65% to 70% [18]. Most centers offer surgical intervention for stage II TTTS (recipient polyhydramnios, donor oligohydramnios and non-visualized bladder) and beyond, while some advise earlier intervention (stage I), to maximize fetal and neonatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…3 Initially, survival of both twins after fetoscopic laser surgery was reported in 18-62% of cases with a singleton survivor in 65-93% of the cases. 4 In established, high-volume centers with experienced operators and earlier interventions, dual and singleton survival rates are now documented to be 70% and 90%, respectively. 3,5 The incidence of donor, recipient, or donor and recipient demise, however, still remains a significant issue with recent series demonstrating a rate of donor demise of 13-54% and a rate of recipient demise of 9-24%.…”
Section: Level Of Evidence: IIImentioning
confidence: 98%
“…The median procedure to death interval was 4 days (range 1-89 days). Risk factors for donor death were fetal growth discordance greater than 30% (odds ratio [OR] 6.7, 95% confidence interval [CI] 2-23), reverse end-diastolic velocity in the donor umbilical artery (OR 25.0, 95% CI 2-290), a marginal and velamentous cord insertion (OR 4.4, 95% CI [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and an increased number of anastomoses (OR 1.2, 95% CI 1.1-1.5). All four donors with both fetal growth discordance greater than 30% and reverse enddiastolic velocity in the donor umbilical artery resulted in a demise.…”
mentioning
confidence: 99%
“…The predominant therapeutic intervention is selective laser ablation of the anastomoses, which can improve the survival and the outcome of the surviving twins [2] . There is also an increased risk for vascular limb ischemia which might be independent of the TTTS and fetal therapy [3] .…”
Section: Discussionmentioning
confidence: 99%